Application of cumulative odds logistic model on risk factors analysis for sexually transmitted infections among female sex workers in Kaiyuan city, Yunnan province, China. Issue 4 (21st January 2009) - Wang, H; Wang, N; Bi, A; Wang, G; Ding, G; Jia, M; Lu, L; Smith, K
Abstract : Objectives: To investigate the epidemiology of sexually transmitted infections (STI) among female sex workers (FSW) in Kaiyuan city, Yunnan province, China, and to identify risk factors associated with STI. Methods: A cross-sectional study of 737 FSW was carried out from March to May 2006, with confidential interviews and laboratory tests for STI. A cumulative logit model was used to evaluate the risk factors for STI. Results: The overall prevalence of HIV is 10.3%. The prevalence of syphilis, herpes simplex virus type 2, gonorrhoea, chlamydia and trichomonas was 7.5%, 68.1%, 8.3%, 25.9% and 10.6%, respectively. In multivariate cumulative odds logistic analysis, the factors associated with STI were education level, living in the entertainment location, injection drug use, non-injection drug use, over five clients in the previous week and inconsistent use of condoms with clients. Conclusion: The findings highlight the gravity of the STI epidemic among FSW in China, where sexual transmission has now overtaken unsafe injection practices as the dominant mode of HIV transmission. Targeted intervention programmes for FSW should focus on increasing condom use, strengthening knowledge and awareness of STI/HIV and encouraging routine screening and treatment-seeking behaviours. Reducing the spread of STI also has profound implications for the prevention of HIV.